2022
DOI: 10.1111/jols.12341
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity on Malaysian corporate boards: a law and social movements perspective

Abstract: This article is a unique investigation of the interaction between sociocultural perceptions of women in Malaysia and reforms implemented in that jurisdiction to promote gender diversity on corporate boards. It adopts a law and social movements perspective to better understand the legal reforms that have emerged, often amid fraught interactions between the state and women's rights activists due to their conflicting conceptions of gender roles. The article draws on empirical data to shed light on the practical w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The positive association between independent female directors and the level of net operating WC may be driven by newly hired female directors in the Malaysian context [1]. As reported by Chen et al (2022), there is a limited pool of women with the requisite experience for Malaysian companies to draw from. Accordingly, newly appointed female directors may have reduced risk-taking incentives because of insufficient experience in leadership positions, resulting in more conservative WCM strategies.…”
Section: Regression Analyses and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive association between independent female directors and the level of net operating WC may be driven by newly hired female directors in the Malaysian context [1]. As reported by Chen et al (2022), there is a limited pool of women with the requisite experience for Malaysian companies to draw from. Accordingly, newly appointed female directors may have reduced risk-taking incentives because of insufficient experience in leadership positions, resulting in more conservative WCM strategies.…”
Section: Regression Analyses and Discussionmentioning
confidence: 99%
“…Note1. Recently, Malaysia adopted reforms aimed at increasing gender diversity on corporate boards through the Malaysian Code on Corporate Governance (Malaysian Code), which was revised in 2017 to require large companies to have at least 30% women on their board of directors(Chen et al, 2022).…”
mentioning
confidence: 99%
“…No universal typology was found in the literature for classifying the glass ceiling antecedents and have been classified differently by diverse authors and organisations (Taparia & Lenka, 2022). On the basis of the literature review, barriers women face in their journey to corporate boards, have been classified into three types of barriers namely societal, individual, and organisational barriers, but it was observed that all these hindering factors are mostly interrelated (Chawla & Sharma, 2016, Chen et al, 2022; Tripathy, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Research has gestured to the influence of public activism, with the appointment of women directors often used to signal the firm's alignment with values of social justice and equality (Ghauri et al, 2021; Perrault, 2015; Rose & Bielby, 2011; Spear & Roper, 2013). Some have addressed the influence of activism on board appointments (Briscoe & Gupta, 2016; Buchter, 2021; DeCelles et al, 2020; Perrault, 2015), the way that global activism interacts with local conditions (Chen et al, 2022; Clark et al, 2022; Seierstad et al, 2017) and the intercepting of social movements by other campaigns (Geletkanycz, 2020). A popular thread of literature on board gender diversity has examined the introduction of regulatory initiatives such as quotas and “comply or explain” regimes, finding that it has served to increase the number of women on boards, but with the risk of tokenism and “golden skirts” among the most privileged women in society (Clark et al, 2022; De Vos & Culliford, 2014; Huse et al, 2011; Seierstad & Opsahl, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%